Energy, exergy, economic and environmental analyses and optimization of a novel vapor injection autocascade heat pump for high-temperature water heating. (1st September 2022) - Chen, Jiaheng; Chen, Qi; Qin, Xiang; Wang, Dingbiao
Highlights: A novel high-temperature vapor injection autocascade heat pump is proposed. Energy, exergy, economic and environmental analyses are conducted by simulation. The novel system improves the heating efficiency by 51.8% over the baseline system. Single-objective optimization can improve the heating efficiency by 12.4%∼14.0%. Multi-objective optimization is conducted to obtain the optimal solution. Abstract: Aiming to develop a high-efficiency and low-cost high-temperature heat pump with large temperature lift ability, a novel vapor injection autocascade heat pump for high-temperature water heating is proposed in this paper. The proposed system utilizes the vapor injection technique to improve the limited performance of the conventional autocascade system and can achieve outstanding heating performance with over 100 °C heating temperature. The energy, exergy, economic and environmental performance of the proposed system are investigated by simulation method and compared with those of the conventional autocascade heat pump. The proposed system averagely improves the heating coefficient of performance and capacity by 51.8% and 104.3% over the conventional system when the evaporating temperature ranges from 0 °C to 20 °C, respectively. The exergy analysis indicates that the excellent exergy performance of the proposed system mainly benefits from the irreversible loss reductions in the throttling valves and cascade condensers. The proposed system possesses the lowest energy cost except for the coal-fired boiler, and produces the minimum pollutant emission except for the gas-fired boiler. The heating coefficient of performance of the proposed system is improved by 12.4% ∼ 14.0% through single-objective optimization. The optimal coefficient of performance and levelized cost of energy are 2.59 and 0.070 $ kWh −1, respectively.